Dielectric metasurfaces based on a phase singularity in the region of high reflectance - Jang Jaewon; Park Minsu; Kang Hyeonjeong; Han Gyu-Won; Cho Hui Jae; Park Yeonsang (Nanophotonics)
Metasurfaces, two-dimensional planar optical devices based on subwavelength-scale structures, have garnered significant attention for their potential to replace conventional optical components in various fields. These devices can manipulate the amplitude, phase, and polarization of light in versatile ways, offering complex functionalities within a single, space-efficient device. However, enhancing their functionality remains a challenge, requiring an expansion in the design flexibility of the structural elements, known as meta-atoms. In this study, we revealed that by varying the two independent lengths of the cross-shaped structure at a wavelength of 980 nm, a phase singularity exists in the region of high reflection. In addition, we found that the phase of transmitted light can be modulated from 0 to 2π by encircling this singularity. Based on the identified phase singularity, we designed and fabricated a polarization-independent metalens with varying numerical apertures to experimentally validate the feasibility of high-reflectivity transmissive wavefront engineering metasurfaces. The introduced meta-atoms based on a phase singularity are expected to open new avenues for applications, such as those requiring light attenuation and concentration simultaneously or the development of resonant cavity structures capable of beam modulation.